2018
DOI: 10.32419/jppni.v3i1.99
|View full text |Cite
|
Sign up to set email alerts
|

Pengalaman Perawat dalam Menerapkan Manajemen Pengendalian Infeksi di RSUP H. Adam Malik Medan

Abstract: AbstrakPencegahan dan Pengendalian Infeksi (PPI) rumah sakit adalah kegiatan yang meliputi perencanaan, pelaksanaan dan pengawasan serta pembinaan dalam upaya menurunkan angka kejadian Infeksi Rumah Sakit (IRS) pada pasien atau petugas rumah sakit dan mengamankan lingkungan rumah sakit dari risiko transmisi infeksi yang dilaksanakan melalui manajemen risiko, tata laksana klinik yang baik dan pelaksanaan Kesehatan dan Keselamatan Kerja Rumah Sakit. Tujuan penelitian: mengeksplorasi pengalaman perawat dalam mene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…In 2015, the World Health Organization (WHO) estimated that around 357 million new infections from one of the four infectious diseases occurred each year [8]. In an epidemiological study based on data collected from 2005 to 2012, it was found that the global incidence of gonorrhea in women was 0.8%, while in men, it was found that the global incidence of gonorrhea was 0.6% of the worldwide population in 2012, so that if converted In total, there were 26,819,000 cases of gonorrhea worldwide in men and women aged 15-49 years, where there were 19 cases per 1000 women and 24 cases per 1000 men based on World Bank data in 2012 [9,10]. Globally, the highest incidence of gonorrhea cases is in the African and Western Pacific regions (including China, Indonesia and Australia).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, the World Health Organization (WHO) estimated that around 357 million new infections from one of the four infectious diseases occurred each year [8]. In an epidemiological study based on data collected from 2005 to 2012, it was found that the global incidence of gonorrhea in women was 0.8%, while in men, it was found that the global incidence of gonorrhea was 0.6% of the worldwide population in 2012, so that if converted In total, there were 26,819,000 cases of gonorrhea worldwide in men and women aged 15-49 years, where there were 19 cases per 1000 women and 24 cases per 1000 men based on World Bank data in 2012 [9,10]. Globally, the highest incidence of gonorrhea cases is in the African and Western Pacific regions (including China, Indonesia and Australia).…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, Gonorrhea has become increasingly resistant to antibiotics that were previously sensitive, which has led to fears that Gonorrhea will not cure. Gonorrhea with multiple drug resistance (MDR) was reported by more than 36 countries in the world in 2015 [9][10]. Untreated gonorrhea can lead to more severe complications, such as female infertility, complications in pregnancy and blindness in newborns who are infected during pregnancy.…”
Section: Gonorrhea Resistancementioning
confidence: 99%
“…Asam urat dapat diatasi dengan Bahan alami lainnya yang terkenal karena khasiatnya dalam bidang kesehatan dan kecantikan adalah madu. Menurut penelitian yang dilakukan oleh Situmorang (2009), hasil yang didapatkan adalah adanya perubahan yang baik pada luka yang diberi madu alami, serta menurut Haryanto (2010) madu sering digunakan oleh nenek moyang untuk menyembuhkan luka infeksi. Madu alami memiliki kandungan yang dapat menyembuhkan luka kaki diabetik.…”
Section: Pendahuluanunclassified
“…Hal ini desebabkan oleh penurunan sensasi rasa pada kaki dan bagian tubuh lainnya akan menimbulkan resiko terjadinya luka yang tidak disadari oleh pasien. Hal ini sesuai dengan pendapat Situmorang (2009) yang menyatakan bahwa komplikasi yang sering terjadi pada pasien diabetes mellitus adalah perubahan patologis anggota gerak ekstremitas bawah akibat gangguan sirkulasi, penurunan sensasi dan hilangnya fungsi saraf sensorik yang bisa menyebabkan luka atau tidak terkontrolnya infeksi sehingga dapat mengakibatkan luka diabetic.…”
Section: Pendahuluanunclassified